Cloud Security And Electronic Transaction Security: : Merger For Online Crime Mitigation - Haruna Ishola Abdullahi (International Journal of Information Systems and Informatics, 2023)
The insecurity of cloud leads to loss or exposure of vital information thereby threatens online transactions. These unfortunate happenings resulted in financial loss, reduced patronage of cloud services and investment diversions. Therefore, this chapter assesses cloud security and electronic transaction security. The chapter adopts qualitative research method, data were sourced secondarily through content analysis of edited books, peer-reviewed journals and credible online resources. It was descriptive in nature and thematically analyzed. The paper anchors on routine activity theory and broken windows theory. Findings revealed that cloud activities are under internal security threats of the cloud service providers and external threats of other users of cloud services. The chapter recommends proper background checks for the staff of the cloud service providers, public enlightenment on cloud security protocols. This chapter will be useful to individuals, cloud services providers, NGOs and researchers in the field of online crimes.